Feminism In Enola Holmes 2 John Fiske Study - Fayyad, Muhammad; Teguh, Salsabila Ayudya; Widianti, Aisah Nur (Journal of English Education, Literature and Linguistics, 2023)
Enola Holmes 2 movie tells a story about the life of a woman named Enola. In this film, the female character is depicted as an active narrative object and carries the message of feminism. The feminism topic attracted the attention of researchers because, so far, women have been often portrayed only as a passive narrative object and even as the main erotic object in the film. This research is to find out the meaning of the semiotic code regarding feminism at the levels of reality, representation, and ideology. Researchers use a qualitative approach with semiotic analysis based on codes from television, which are divided into three levels: reality, representation, and ideology. The results of the research show the values of feminism at the level of reality through codes of appearance, make-up, dialogue, way of speaking, environment, and behavior. On the levels, representation of feminist values is shown through camera code, characters, actions, conflicts, and dialogue. On an ideological level, the values of feminism represent the close and inseparable relationship between women and nature. Keywords: Representation, Feminism, Film, Semiotic, John Fiske.